Incidence Rate, Risk Factors And Coverage Of Brucellosis Vaccination In Naibone, Sasitamean District, Malaka Regency - Anjelina Lidia Bouk; Maxs U.E Sanam; Annytha I. R Detha (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2022)
Brucellosis is one of the strategic infectious animal diseases in Indonesia. Malaka regency is one of the regencies in East Nusa Tenggara with a prevalence of Brucellosis >2%. The purpose of this study was to determine the level of incidence, risk factors and coverage of Brucellosis vaccination in Naibone. The research method used is a questionnaire and interview. The frequency of Brucellosis incidence based on clinical symptoms in Naibone is 9,4%. The clinical symptoms of brucellosis found in this study were abortion as much as 13,3% with the percentage who experienced abortions in late pregnancy was 9,4%. Factors that support the incidence rate of Brucellosis in the study are maintenance management is semi intensive, management of aborted cows and fetuses with poor abortion product. Aborted cows were not separated from the herd and 76% of aborted fetuses were left, 12% was buried, 12% was given to dogs. The level of education of farmers in Naibone Village is still low and vaccination is not yet effective. Vaccination coverage in Naibone is still not effective at 20%.